Probation supervision in the Netherlands - Boone, Miranda (The Routledge handbook on global community corrections, 2024)
Probation services in the Netherlands are private nonprofit organizations that are fully financed by the national Government and perform three main tasks: advise, supervision, and community services. The focus is on preventing recidivism and supporting people under supervision to live a crime-free life. The organizations have a unique position in the criminal justice system, working with suspects in the pre-trial phase period shortly after their arrest until sentencing and supervising people who spend the last phase of a prison sentence in the community, people convicted to a suspended sentence, and community sentences. Therefore, probation services cooperate with other criminal justice organizations, healthcare, social services, and local authorities to reach its aims. Recently, probation services intensified cooperation with prison staff in prisons in order to improve detention and reintegration plans and offer support during detention. On average, supervision lasts two years. Three levels of intensity can be disseminated that may vary during supervision. Of the legally defined conditions, treatment is the most imposed. People under supervision have a voice in the implementation or decision-making during supervision, e.g., in the procedure around developing supervision plans and in the decision-making process in cases of breach. The proportion of supervision orders that end unsuccessfully is around 25%. About 35% of the people under supervision are convicted for a new offense during or within two years after supervision. Recent developments in the Dutch probation services are a growing victim awareness, more involvement of volunteers during supervision, and intensifying local cooperation.